Effects of Encapsulated Fish Oil by Polymerized Whey Protein on the Textural and Sensory Characteristics of Low-Fat Yogurt - Liu Diru; Zhang Tiehua; Jiang Nan; Xi Chunyu; Sun Chunyan; Zheng Jian; Guo Mingruo (Polish Journal of Food and Nutrition Sciences)
Five types of polymerized whey protein (PWP1, PWP2, PWP3, PWP4 and PWP5) containing different amounts of fish oil were added to low-fat yogurt as fat replacers. The texture, apparent viscosity, and sensory properties of the yogurts were analyzed in comparison with full-fat ( 3.0%, w/w, fat) and low-fat (1.5%, w/w; and 1.2%, w/w) milk yogurt controls. The majority (~85%) of the particle size distribution was in the range of 1106±158 nm. Thermal property analysis indicated PWP was thermally stable between 50°C and 90°C. Yogurts formulated with 12% of PWP4 and 14% of PWP5 demonstrated higher firmness, springiness and adhesiveness (P<0.05), and lower cohesiveness (P<0.05) than the low-fat milk yogurt controls. There was no fat separation and they had less fishy smell. Yogurts incorporated with 12% of PWP4 had comparable sensory and textural characteristics to the full- -fat milk yogurt control.